Membrane current oscillations in descending vasa recta pericytes - Zhang, Qingli (American Physiological Society, 2008)
We investigated the origin of spontaneous transient inward current (STIC) oscillations in descending vasa recta (DVR) pericytes. In cells clamped at −80 mV, angiotensin II (ANG II; 10 nmol/l) induced oscillations with mean amplitude and frequency of −65.5 pA and 1.2 Hz. Simultaneous recording of cytoplasmic calcium ([Ca(2+)](CYT)) and membrane current oscillations verified their synchrony and the correlation of their amplitudes. Confocal recording in fluo-4-loaded DVR showed that ANG II can induce either stable pericyte [Ca(2+)](CYT) elevation or oscillations, while decreasing adjacent endothelial [Ca(2+)](CYT). Oscillating currents reversed sign at −30.2 mV and were blocked by niflumic acid, implicating charge transfer via Cl(−) ion. Removal of extracellular Ca(2+), blockade of Ca(2+) influx with SKF96365 (30 μmol/l), ryanodine (30 μmol/l), or caffeine (10 mmol/l) inhibited oscillations. In contrast, they were insensitive to removal of extracellular Na(+) and exposure to either nifedipine (1 μmol/l) or 2-aminoethoxydiphenyl borate (10 μmol/l). Ouabain (100 nmol/l) increased basal pericyte [Ca(2+)](CYT) and the frequency of resting STICs but did not affect the larger oscillations that followed ANG II stimulation. We conclude that [Ca(2+)](CYT) oscillations stimulate Cl(−) currents. The former are most likely maintained by repetitive cycles of ryanodine-sensitive SR Ca(2+) release and SKF96365-sensitive store refilling.